Chlamydospore Formation during Hyphal Growth in Cryptococcus neoformans - Lin, Xiaorong (American Society for Microbiology, 2005)
Cryptococcus neoformans, a basidiomycetous fungal pathogen, infects hosts through inhalation and can cause fatal meningoencephalitis in individuals if untreated. This fungus undergoes a dimorphic transition from yeast to filamentous growth during mating and monokaryotic fruiting, which leads to the production of hyphae and airborne infectious basidiospores. Here we characterized a novel morphological feature associated with the filamentous stages of the life cycle of C. neoformans which resembles resting or survival structures known as chlamydospores in other fungi. The C. neoformans chlamydospore-like structure is rich in glycogen, suggesting that it might have a role as an energy store. However, characterization of mutants with decreased or increased levels of glycogen production showed that glycogen levels have little effect on filamentous growth, sporulation, or chlamydospore formation. These results suggest that the formation of chlamydospores is independent of glycogen accumulation level. We also show that chlamydospore formation does not require successful sporulation and that the presence of chlamydospores is not sufficient for sporulation. Although the biological functions of chlamydospores remain to be established for this pathogenic fungus, their formation appears to be an integral part of the filamentation process, suggesting that they could be necessary to support sexual sporulation under adverse conditions and thereby facilitate the production of infectious basidiospores or long-term survival propagules in harsh environments.